EFFICACY OF USING CULTURE MEDIA IN ASSISTED REPRODUCTIVE TECHNOLOGY PROGRAMS (Experimental biology, 2022)
One of the steps to successfully solve the problem of human infertility is the development and improvement of culture media used for the cultivation of embryos in ART programs.  In the past, significant progress has been made in this direction - single-step and two-step culture media have been developed. Both media are widely used in practice to improve the efficiency of individual ART results. The aim of this work was to determine the effectiveness in usage of commercial culture media (Continuous Single Culture Irvine and Origio Sequential Cleav/Blast) in IVF and ICSI programs. A comparative analysis of their impact on embryo quality, fertilization and pregnancy outcomes in IVF and ICSI programs at the Embryology Laboratory of LLP “Centre ECO” in 2017-2021 was conducted. 2650 programs took place, of which 760 programs accounted for IVF and 1890 programs for ICSI. The results of the analysis revealed no significant differences in the use of the above-mentioned media to obtain good quality blastocysts in the IVF program. The usage of the studied culture media showed a higher level of obtaining blastocysts of optimal quality in the ICSI programs when cultured in single-step medium compared to sequential medium. The difference between the two relative values was statistically significant (t=8.08; p0.001). Comparative analysis of the results of embryo cultivation in different nutrient media allow us to conclude that both single-step and sequential culture media, equally contribute to the quality development of blastocysts and demonstrate positive clinical results. Program efficacy based on the factor of ART program ending in pregnancy using CSC Irvine nutrient media was 46.44% for IVF, and 41.42% for ICSI.  Culturing embryos in Origio Sequential Cleav/Blast medium in IVF programs showed pregnancy outcomes at 49.51%, in ICSI programs - 42.85%.
Keywords: infertility, embryo, culture/nutrient medium, IVF, ICSI.